The Reluctance Phenomenon of Islamic Banks to Offer Profit-Loss Sharing Financing - Sabrina, Sabrina; Majid, M. Shabri Abd (Universitas Negeri Semarang, 2020)
This study contributes to the existing literature on the phenomenon of lower valume of Profit-Loss Sharing (PLS)-based products offered by Islamic banks by comprehensively discussing and analyzing the issue from the internal, external, and regulation perspectives, taking the case of PT. Bank Aceh Syariah (BAS) in Indonesia. Using a grounded theory approach, this study interviews selected informants who are knowledgeable in Islamic economics, banking, and financial theories and practices, including experts, practitioners, customers, and regulators. Viewed from three aspects, namely: internal, external, and regulation, the study found that, from the internal aspect, the problem of the low volume of PLS-based financing products is caused by six factors, namely: high risk, lack of quality and quantity of human resources, complicated handling, lack of banking product innovation, asymmetric information, and lack of socialization. Meanwhile, from the external aspects, it is caused by three factors, namely: moral hazard, lack of community's knowledge of Islamic banking products, and low demand. Finally, from the aspect of the regulation, it is caused by a lack of supportive regulation. By tackling these issues, it is believed that the Islamic bank could offer more PLS-based products that finally contribute to the prosperity of the public.